2020
DOI: 10.1007/s00345-020-03084-4
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between glucose homeostasis status and prostate size in aging Chinese males with benign prostatic hyperplasia

Abstract: Purpose Increasing evidence shows that many metabolic factors are involved in the progression of benign prostatic hyperplasia (BPH). We aimed to assess the relationship between the status of glucose homeostasis and prostate size in aging Chinese males undergoing transurethral resection of the prostate (TURP) for BPH. Methods A total of 1006 medical records of BPH patients undergoing TURP were reviewed. Prostate size was measured by transrectal ultrasound. Annual total prostate (TP) and transitional zone (TZ) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Metabolic syndrome and its components of obesity, hyperinsulinemia, T2DM, dyslipidemia, and hypertension are significantly associated with BPH [ 89 90 91 92 93 ]. Therefore, metformin may not only reduce the risk of BPH via a direct effect on the prostate tissue, it may also act through indirect effects by correcting the metabolic dysregulations in the various components of metabolic syndrome.…”
Section: Prostate-related Healthmentioning
confidence: 99%
“…Metabolic syndrome and its components of obesity, hyperinsulinemia, T2DM, dyslipidemia, and hypertension are significantly associated with BPH [ 89 90 91 92 93 ]. Therefore, metformin may not only reduce the risk of BPH via a direct effect on the prostate tissue, it may also act through indirect effects by correcting the metabolic dysregulations in the various components of metabolic syndrome.…”
Section: Prostate-related Healthmentioning
confidence: 99%
“…This finding was consistent with previous studies which found that there was an association between hyperglycemia and prostate size and that abnormal glucose was correlated with prostate enlargement. In patients younger than 70 years, compared with the normal glucose group, the adjusted odds ratio for prostate volume enlargement in the prediabetic group and the diabetic group was 2.27 (95% CI 1.29 -4.00) and 4.74 (95% CI 2.18 -10.30) respectively (6). Prostate volume was found to be higher in patients with HbA1c levels ≥6.5% (45.69±3.97 vs. 36.64±3.30) (7) While the precise mechanism was still unclear, there are several proposed mechanisms on how blood glucose could impact prostate enlargement.…”
Section: Discussionmentioning
confidence: 93%
“…Evidence showed that hyperglycemia is considered to take part in the development of prostate enlargement (6). Although, the association between the two is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical guidelines state that choosing the appropriate surgical procedure according to the prostate size can reduce complications and is vital to improving patients’ quality of life ( 21 23 ). Although hyperglycemia has been reported to increase prostate volume ( 24 , 25 ), and lymphocytes, free/total prostate-specific antigen ( 26 ), neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and lymphocyte-to-monocyte ratio have been associated with BPH ( 27 ), these did not analyze in detail or separately the relationship between prostate volume and hematological parameters. An analysis of platelet and monocyte-to-lymphocyte ratio and diabetes mellitus with benign prostatic enlargement is not reported in related article.…”
Section: Introductionmentioning
confidence: 99%